2021
DOI: 10.1088/1361-6463/ac0b70
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of angularly resolved EUV emission from 2-µm-wavelength laser-driven Sn plasmas using preformed liquid disk targets

Abstract: The emission properties of tin plasmas, produced by the irradiation of preformed liquid tin targets by several-ns-long 2 µm-wavelength laser pulses, are studied in the extreme ultraviolet (EUV) regime. In a two-pulse scheme, a pre-pulse laser is first used to deform tin microdroplets into thin, extended disks before the main (2 µm) pulse creates the EUV-emitting plasma. Irradiating 30-to 300 µm-diameter targets with 2 µm laser pulses, we find that the efficiency in creating EUV light around 13.5 nm follows the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Schupp et al [72,78] and Behnke et al [34] recently reported the first experimental study of 2 µm laser-driven tin plasmas. These studies, discussed in section 3.3, confirmed the simulation results with regards to the particular promise of the 2 µm driver.…”
Section: Main Pulse: Using Solid-state Lasers To Drive Euv Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schupp et al [72,78] and Behnke et al [34] recently reported the first experimental study of 2 µm laser-driven tin plasmas. These studies, discussed in section 3.3, confirmed the simulation results with regards to the particular promise of the 2 µm driver.…”
Section: Main Pulse: Using Solid-state Lasers To Drive Euv Emissionmentioning
confidence: 99%
“…In a detailed follow-up work, Schupp et al [78] reported on the EUV emission properties of tin plasmas produced by the irradiation of pre-pulse-preformed liquid tin targets by 2 µm wavelength laser pulses (cf figure 8). In a two-pulse scheme, much like in the current industrial setting, a pre-pulse laser is first used to deform tin microdroplets into thin, extended disks (cf figure 8(c)) before the main (2 µm) pulse creates the EUV-emitting plasma.…”
Section: Comparing Plasmas Driven By 1 and 2 µM Wavelength Lasersmentioning
confidence: 99%
“…3 Consistently, twofold higher CEs have been found using 2 lm laser light, under otherwise comparable conditions. [16][17][18] However, the experiments using focused 2 lm light did not yield CE values competitive with the CO 2 state-of-the-art, with maximum CEs being limited to approximately 3%-and no information on 2 lm laser-driven source size is currently available. It was hypothesized 17,25,26 that CE values could increase significantly if the plasma is heated homogeneously, i.e., in a manner that is constant spatially and temporally to generate a uniform (optimum) temperature plasma.…”
mentioning
confidence: 99%
“…9,[11][12][13][14] Combined with the low wall-plug efficiencies of 10 lm gas lasers, this has motivated research into plasmas driven by shorter wavelength, highly efficient solid-state lasers to strongly accelerate in recent years. [15][16][17][18][19][20][21] Radiationhydrodynamic simulations have shown promise of high CE plasma sources driven by 2-5 lm lasers 13 without the need for complex target shaping. Given the maturity of 1.064 lm solid-state laser technology, and the strong progress in 1.88 lm laser development, 20,21 studies have focused on tin plasmas generated by 1-and 2 lm laser light.…”
mentioning
confidence: 99%
See 1 more Smart Citation